Impact of needle insertion depth on the removal of hard‐tissue debris. (19th May 2016) - Perez, R.; Neves, A. A.; Belladonna, F. G.; Silva, E. J. N. L.; Souza, E. M.; Fidel, S.; Versiani, M. A.; Lima, I.; Carvalho, C.; De‐Deus, G.
Abstract: Aim: To evaluate the effect of depth of insertion of an irrigation needle tip on the removal of hard‐tissue debris using micro‐computed tomographic (micro‐CT) imaging. Methodology: Twenty isthmus‐containing mesial roots of mandibular molars were anatomically matched based on similar morphological dimensions using micro‐CT evaluation and assigned to two groups ( n = 10), according to the depth of the irrigation needle tip during biomechanical preparation: 1 or 5 mm short of the working length (WL). The preparation was performed with Reciproc R25 file (tip size 25, .08 taper) and 5.25% NaOCl as irrigant. The final rinse was 17% EDTA followed by bidistilled water. Then, specimens were scanned again, and the matched images of the canals, before and after preparation, were examined to quantify the amount of hard‐tissue debris, expressed as the percentage volume of the initial root canal volume. Data were compared statistically using the Mann–Whitney U ‐test. Results: None of the tested needle insertion depths yielded root canals completely free from hard‐tissue debris. The insertion depth exerted a significant influence on debris removal, with a significant reduction in the percentage volume of hard‐tissue debris when the needle was inserted 1 mm short of the WL ( P < 0.05). Conclusions: The insertion depth of irrigation needles significantly influenced the removal of hard‐tissue debris. A needle tip positioned 1 mm short of the WL resulted in percentage levels of hard‐tissue debris removal almost three times higher than when positioned 5 mm from the WL.